Le role de l'homme dans l'alteration de l'environnement du Mema sous l'ancien royaume du Ghana - Haaland, G. (CIPEA, 1980)
Summary and interpretation of the findings of an archaeological investigation of the Mema area of central Mali, particularly. effect of human activities specially iron smelting and subsistence farming on the present environment feature of the area.